Scoping review of veterans’ disclosure of mental health concerns or medical conditions in the workplace and other settings: study protocol - Laura J Ferris; Emma B Knight; Richard O’Quinn; Tarli Young; Justin P Brienza (BMJ Open)
Introduction Veterans deal with ‘unobservable’ medical or mental health conditions, such as post-traumatic stress disorder, at higher rates than the general population. Disclosure of such conditions is important to provide social, emotional, medical and mental health support, but veterans may face challenges when deciding whether to disclose conditions, including fear of stigma or discrimination. Safe disclosure in the workplace is particularly important, as it allows employees to gain accommodations and enables employers to manage workplace health and safety effectively. The objective of this study is to investigate the state of the literature on veterans’ disclosure of mental health concerns or medical conditions and identify how it has been studied in the workplace context.Methods and analysis To conduct the scoping review, several databases will be searched between 10 November 2023 and September 2024 including PubMed, Scopus, Embase, Web of Science, PsycInfo, CINAHL and Cochrane Library, as well as theses databases. Sources will be uploaded to Covidence where two investigators will independently conduct title/abstract and full-text screening, with any conflicts resolved to consensus via discussion with a third investigator. Studies will be included if they are empirical, original research, focused on veterans and disclosure of mental health concerns or medical conditions and written in English. After inclusion, study information will be extracted including key findings about contexts, correlates, processes and outcomes of disclosure in compliance with Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews.Ethics and dissemination The scoping review will provide insight into the state of the literature on veterans’ disclosure of mental health or medical conditions, particularly in the workplace. Ethical approval is not required as the scoping review will be informed by publicly available data. Findings may be shared through journal articles or conference presentations, and recommendations will be provided to inform future research aimed at improving disclosure processes and outcomes. The scoping review has been pre-registered (https://osf.io/uxrjp).